Boko Haram's attacks and the people's response: A 'fourth pillar' of the responsibility to protect?. Issue 2 (2nd April 2016) - Popovski, Vesselin; Maiangwa, Benjamin
ABSTRACT: This article examines the failure of the Nigerian government to exercise its responsibility to protect (R2P) populations from mass atrocities in the wake of Boko Haram's violent and persistent attacks against civilians in north-east Nigeria. After the abduction of 276 schoolgirls on 14 April 2014, the affected communities engaged directly in protecting their villages and families. Another murderous and devastating attack on Baga in January 2015 and the abduction of over 400 women in Damasak in March 2015 continued to expose the governmental failure to protect people at risk of losing their lives. This article examines the dynamics of the people's response to the crisis and investigates whether this response could be conceptually defined as a 'fourth pillar' of R2P, when a state – even in collaboration with the international community – is unable to live up to its R2P. Certainly, such a phantom 'fourth pillar' is symbolic and should not be used in any way by governments to re-delegate their first pillar primary R2P.